Improvements and Safety Analysis on the Technologies of Current Nuclear Power Systems for Remote Places and Outer Space - Julio de Oliveira Jr.; Dmitry Samokhin (Brazilian Journal of Radiation Sciences)
A new age of space nuclear reactors is at hand. Current developments in both energy generation and thermal energy conversion are fueling new reactor designs. Some projects have already been tested on Earth, and the results were considered optimistic. This work discusses the latest designs in space nuclear reactors and their surrounding technologies in order to propose new improvements, further expanding their variety and possibilities. The objective was to identify the most promising new designs and propose updates to them that would increase the safety and performance. Furthermore, this work was realized in the scope of the safety analysis of the projects, calculating and simulating in the SAPHIRE software package the consequences of changing parts and comparing the reliability of each possible configuration. At the end, it is discussed which of the designs are considered to be better for new space projects involving nuclear power systems. The work also takes into account new technology that was not available during the development of the older designs. It is possible to conclude that the subject is very dense, and that there are several different aspects that should be taken into account when choosing the ideal space nuclear reactor for each mission, program, and country. Four different concept designs were proposed, by changing around with the pieces of known designs. Two of them by simply changing the converter systems of NASA’s KRUSTY design, and two reactors for space based on molten salt reactors. All of them using the KRUSTY systems as a basis, as they are the most well documented ones in the scope of safety analysis.  The proposals based on NASA were less efficient, achieving from 0.6 to 0.8 kWe, but were even more reliable, in one of the cases twice as much. The proposals based on the molten salt reactor were more open ended, and the estimates should be considered carefully. The power output for the two molten salt proposals ranged from 60 to 75 kWe, and their reliability was comparable to the KRUSTY design. Even though is only an initial theoretical approach, this work succeeded in proposing new designs and highlighting their safety aspects over the known ones. The data is likely to be refined in the future, but the results are promising.